Rekonstruksi Tari Jepin Langkah Jarom Mesen Di Kabupaten Kubu Raya - Kurniasih, Arum; Dwi Oktariani; Aline Rizky Oktaviari Satrianingsih (Prodi Pendidikan Sendratasik FKIP UMTAS, 2024)
This research aims to describe the process and results of the Jepin Langkah Jarom Mesen Dance reconstruction activities in Kubu Raya Regency. The problem in this research relates to the existence and condition of Jarom Mesen's Jepin Step Dance which has long been lost and its dance form which is no longer intact today. Researchers used descriptive research methods, qualitative research forms, as well as choreographic and ethnochoreological approaches. The data sources in this research are Mr. Sabaruddin (70), Mr. Edy Arfandi (58) Arfandi, and Mr. Ramlan Tharsono (60) who are the original performers of the Jepin Langkah Jarom Mesen Dance. Data collection techniques in this research include observation, interviews and documentation. Techniques for testing the validity of data use extended observations and source triangulation. The results of this research show that the reconstruction process was carried out in 3 stages, namely excavation, rearrangement and validation. This reconstruction process produces variety 1, variety 2, and variety 4. Jepin Langkah Jarom Mesen dance is presented using Kurong clothes for female dancers and Telok Belanga for male dancers with realistic make-up. The characteristic of Jepin Langkah Jarom Mesen Dance is in 3 variations with the movement of clapping your hands above your head and lifting your legs alternately.